2009
DOI: 10.1002/jhet.110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel conjugated coumarin‐thiazole systems

Abstract: in Wiley InterScience (www.interscience.wiley.com).Seven new 2,4-disubstituted thiazoles have been synthesized by Hantzsch condensation and assayed for several biological activities for a preliminary screening. They have been fully characterized by elemental analysis, UV-Vis spectroscopy, TG-DTA, IR, and 1 H NMR as well. These structures display different pharmacological (antimicrobic activity, citotoxicity, and hMAO inhibition) and industrial properties (complete transparency in the region between 465-800 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…In particular, these studies confirmed that thiazole derivatives are good pharmacophores for the design of bioactive molecules [12,13] as bioisoster of the imidazole ring, and it emerged a different mode of action, inhibiting the fungal biofilm growth, in relation to azoles and ampothericin B, a low toxicity profile, and a broad fungicidal spectrum [14]. For these reasons and pursuing our research in the field [15,16], in this paper we report on the synthesis and the biological evaluation (in vitro antifungal activity and synergy with clotrimazole) of a new series of 2,4-disubstituted-1,3-thiazoles bearing a bicyclic or heterocyclic ring on double bond C]N and a 4 0 -substituted (CH 3 , OCH 3 ) phenyl in position C2 and C4 of thiazole nucleus, respectively ( Table 1). The choice of these electron-releasing substituents on the aryl ring derived from the structure-activity relationships we extrapolated in our previous work [15].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In particular, these studies confirmed that thiazole derivatives are good pharmacophores for the design of bioactive molecules [12,13] as bioisoster of the imidazole ring, and it emerged a different mode of action, inhibiting the fungal biofilm growth, in relation to azoles and ampothericin B, a low toxicity profile, and a broad fungicidal spectrum [14]. For these reasons and pursuing our research in the field [15,16], in this paper we report on the synthesis and the biological evaluation (in vitro antifungal activity and synergy with clotrimazole) of a new series of 2,4-disubstituted-1,3-thiazoles bearing a bicyclic or heterocyclic ring on double bond C]N and a 4 0 -substituted (CH 3 , OCH 3 ) phenyl in position C2 and C4 of thiazole nucleus, respectively ( Table 1). The choice of these electron-releasing substituents on the aryl ring derived from the structure-activity relationships we extrapolated in our previous work [15].…”
Section: Introductionmentioning
confidence: 66%
“…The new derivatives were synthesized successfully as reported in our previous communications [15,16,18]. Different carbonyl compounds were reacted directly with thiosemicarbazide with catalytic amounts of acetic acid in 2-propanol and the obtained thiosemicarbazones subsequently were condensed with abromo-4-methyl/4-methoxyacetophenone to 2,4-disubstituted-1,3-thiazoles (Hantzsch reaction) as shown in Scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
“…Actually, in literature, several works demonstrate the anti-fungal activity of coumarin derivatives [24][25][26][27][28][29] .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, halogenated thioureas have anticholinesterase potential [19]. 2,4-Disubstituted thiazoles having coumarin rings displayed different pharmacological properties like, antimicrobic activity, cytotoxicity, and hMAO inhibition [38]. The available treatments for the AD have got short half-life with hazardous side effects, thus demands the need to introduce new therapies.…”
Section: Introductionmentioning
confidence: 99%